Starbucks' Marketing Public Relations: A Beverage or a Lifestyle? - Muhammad Syendi Apriko; Anita Trisiah (Wardah, 2023)
The old Islamic culture of 'drinking coffee' has become integral to Indonesian people's daily lives. The large variety of Cafés also completes the lifestyle of urban people. The Starbucks brand originating from America, has become an option for many coffee lovers, especially in Palembang. Therefore, researchers want to know whether Starbucks is only a food and beverage brand or is it a lifestyle. Conducting desk research and observation methods at four Starbucks outlets in Palembang and using the 4Ps marketing approach and marketing public relations strategy theory, the researchers found that Starbucks is not only a food and beverages outlet but has embedded its brand as a lifestyle and utilizing a theoretical and digital media to further strengthen the existence of the Starbucks brand to consumers and potential customers.